2019
DOI: 10.7717/peerj.6252
|View full text |Cite
|
Sign up to set email alerts
|

Aridity and land use negatively influencea dominant species' upper critical thermal limits

Abstract: Understanding the physiological tolerances of ectotherms, such as thermal limits, is important in predicting biotic responses to climate change. However, it is even more important to examine these impacts alongside those from other landscape changes: such as the reduction of native vegetation cover, landscape fragmentation and changes in land use intensity (LUI). Here, we integrate the observed thermal limits of the dominant and ubiquitous meat ant Iridomyrmex purpureus across climate (aridity), land cover and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 92 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…Maximum monthly temperatures were positively correlated with species CT min but not with species CT max . Finally, Andrew et al (2019) studied thermal tolerance in Iridomyrmex purpureus populations along an aridity gradient, finding a weak increase in both CT max and CT min with increasing aridity.…”
Section: Abiotic and Biotic Determinants Of Ant Thermal Limitsmentioning
confidence: 99%
“…Maximum monthly temperatures were positively correlated with species CT min but not with species CT max . Finally, Andrew et al (2019) studied thermal tolerance in Iridomyrmex purpureus populations along an aridity gradient, finding a weak increase in both CT max and CT min with increasing aridity.…”
Section: Abiotic and Biotic Determinants Of Ant Thermal Limitsmentioning
confidence: 99%
“…Large ant species are especially sensitive to disturbance (Gibb et al., ; Leal, Andersen, & Leal, ), and this can result in severe reductions in the quality of seed dispersal services in disturbed habitats (Almeida et al., ; Gove, Majer, & Dunn, ; Leal, Andersen, & Leal, ; Ness, Bronstein, Andersen, & Holland, ). Although smaller insects are considered more sensitive to high temperatures through desiccation (Baudier, Mudd, Erickson, & O'Donnell, ; Kühsel, Brückner, Schmelzle, Heethoff, & Blüthgen, ), recent studies have found that the most sensitive ants to climate change are in fact the largest (Andrew, Miller, Hall, Hemmings, & Oliver, ; Gibb et al., ). This might be because large ants require more resources and take longer to mature, thus reducing their adaptive capacity (Gibb et al., ; McCain & King, ; Savage, Gillooly, Brown, West, & Charnov, ).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from body size, another organismal trait commonly seen in mesic-adapted arthropods is that they have thinner, more permeable cuticles with fewer hydrocarbons [1,50,51]. Evolutionary adaptations to environmental conditions can cause more xeric-adapted "water conserver" species to be present in cities and more mesic-adapted "water seeker" species to be present in undeveloped locations [33,48,49,[52][53][54][55]. Thus, although terrestrial arthropods in mesic regions (and cooler sites) may infrequently experience water limitation, they may be more greatly affected when droughts or heatwaves occur (hypothesized in McCluney [33]).…”
Section: Plos Onementioning
confidence: 99%